Use of intracavitary-ECG for tip location of femorally inserted central catheters. Issue 1 (January 2022) - Weber, Mark D; Himebauch, Adam S; Conlon, Thomas
Femorally inserted central catheters (FICCs) are frequently required for central access in children. Ultrasound can accurately locate the catheter tip in most cases and its use is increasing in clinical vascular access practice. In patients with poor acoustic windows, intracavitary electrocardiogram (IC-ECG) is an alternative to ultrasound-guidance for FICC positioning. A case series of three patients demonstrate methods of FICC positioning in children. The first patient had excellent acoustic windows and ultrasound-guided FICC positioning is described in conjunction with IC-ECG measurements. The following two patients had poor acoustic windows, thus IC-ECG guided FICC tip position. The use of FICCs in children has increased in recent years. Ultrasound has emerged as a reliable method of assessing FICC tip location. IC-ECG is an accurate and complementary method of assessing FICC tip location, but can be a primary method when ultrasound is not available or cannot directly visualize the catheter. IC-ECG P-wave characteristics identify optimal tip position at the inferior cavoatrial junction and are different from characteristics at the superior cavoatrial junction.